How landscape variables influence the relative abundance, composition, and reproductive viability of macroalgal wrack in a high latitude glacial estuary. (5th January 2023) - Ulaski, Brian P.; Otis, Edward O.; Konar, Brenda
Abstract: Beach-cast wrack is an important resource that is commonly harvested by humans, and its removal can have consequences for coastal ecosystems. To further our understanding of wrack dynamics within high latitude ecosystems, our study objectives were to: 1) quantify spatio-temporal differences in beach-cast wrack biomass and composition, 2) quantify and compare the composition of drifting and beach-cast wrack, 3) determine the reproductive status of beach-cast kelp and rockweed wrack, and 4) compare the efficacy of using drone and on-the-ground surveys to assess beach-cast wrack surface area at different spatial scales. This study was based in Kachemak Bay, Alaska, a high latitude estuarine system where wrack harvest is carefully regulated by the Alaska Department of Fish and Game. Wrack from eleven beaches was surveyed between March and September in 2018 and 2021. Coastline (substrate type, slope, and exposure) and adjacent watershed characteristics (percent glacial cover and range in seawater salinity) were determined for each site and found to correlate with diversity and compositional differences in drifting and beach-cast wrack throughout Kachemak Bay. Reproductive kelp and rockweed wrack were confirmed to be viable at all surveyed sites, which suggests that harvesting wrack has the potential to remove viable propagules from the reproductive pool. On-the-ground and drone-based surveys of beach-cast wrack both revealed similar seasonal patterns of patchy (spring) and continuous (summer) deposition onshore, confirming that aerial drone surveys are a useful and efficient tool for monitoring beach-cast wrack surface area. This study identified several factors that contribute to wrack relative abundance, distribution, composition, and reproductive viability, which can be used by resource managers to develop wrack stock assessment and sustainable harvest strategies. Highlights: Select landscape variables correlate with macroalgal wrack composition. Seasonal input of reproductive kelp and rockweed tissue to beach-cast wrack were viable. Aerial drone surveys provide feasible means of large-scale wrack assessments. Assessment of high latitude wrack dynamics has important management implications.